Analysis of mental disorders in victims of violent crimes - Shum Сергій (Psychosomatic Medicine and General Practice, 2020)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" II Congress. It is dedicated to the analysis of mental disorders in victims of violent crimes.